2021
DOI: 10.3389/fchem.2021.689006
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characteristics of Fusion Peptides Derived From Enveloped Viruses

Abstract: Membrane fusion events allow enveloped viruses to enter and infect cells. The study of these processes has led to the identification of a number of proteins that mediate this process. These proteins are classified according to their structure, which vary according to the viral genealogy. To date, three classes of fusion proteins have been defined, but current evidence points to the existence of additional classes. Despite their structural differences, viral fusion processes follow a common mechanism through wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 106 publications
0
26
0
Order By: Relevance
“…In this context, high-resolution structures of the S protein on isolated SARS-CoV-2 particles have demonstrated that low levels of the S protein trimer disassociate, leaving the S2 domain radiating from the virus envelope in an extended postfusion conformation ( 34 ). It is possible that the freely exposed fusion peptide at the N terminus of the S2 protein may insert into the plasma membrane on infected cells and serve as an alternative transmembrane domain ( 35 ). In such a scenario, this would tether the virus particles to the surface of infected cells and facilitate the localized cell-to-cell spread of infection that we observe.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, high-resolution structures of the S protein on isolated SARS-CoV-2 particles have demonstrated that low levels of the S protein trimer disassociate, leaving the S2 domain radiating from the virus envelope in an extended postfusion conformation ( 34 ). It is possible that the freely exposed fusion peptide at the N terminus of the S2 protein may insert into the plasma membrane on infected cells and serve as an alternative transmembrane domain ( 35 ). In such a scenario, this would tether the virus particles to the surface of infected cells and facilitate the localized cell-to-cell spread of infection that we observe.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, high resolution structures of the S protein on isolated SARS-CoV-2 particles have demonstrated that low levels of the S protein trimer disassociate leaving the S2 domain radiating from the virus envelope in an extended post-fusion conformation [39]. It is possible that the freely exposed fusion peptide at the N-terminus of the S2 protein may insert into the plasma membrane on infected cells and serve as an alternative transmembrane domain [40]. In such a scenario, this would tether the virus particles to the surface of infected cells and facilitate the localized cell-to cell spread of infection that we observe.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that the freely exposed fusion peptide at the N-terminus of the S2 protein may insert into the plasma membrane on infected cells and serve as an alternative transmembrane domain [40]. In such a scenario, this would tether the virus particles to the surface of infected cells and facilitate the localized cell-to cell spread of infection that we observe.…”
Section: Establishing the Kinetics Of Cell-to-cell Spread For Sars-co...mentioning
confidence: 94%
“…Retrovirus Envs are class I fusion proteins, with fusion peptides (FP) located at or near the N-terminus of TM [ 126 , 127 ]. Gamma-type Env can have N-terminal FP, as is found in most gammaretroviruses and deltaretroviruses, or the FP can comprise an internal “loop” near the N-terminus of TM demarcated by disulfide bonded cysteines, as is the case for alpharetroviruses [ 100 ].…”
Section: Hallmark Features Of Gamma-type Envsmentioning
confidence: 99%